Presenting a Model of the Role of Entrepreneurial Leadership in the Performance of Active Small and Medium Businesses in the Field of Nanotechnology in Tehran - Savadkouhi, Mahdi; Yousefi Saeed Abadi, Reza; Fattahi, Majid (Iranian Journal of Educational Sociology, 2022)
Purpose: Entrepreneurial leadership plays an effective role in improving the performance of various businesses including small and medium businesses. As a result, the current research was conducted with the aim of presenting a model of the role of entrepreneurial leadership in the performance of active small and medium businesses in the field of nanotechnology in Tehran.Methodology: The method of this research was of mixed exploratory type (qualitative and quantitative). The population of the present study in the qualitative section was the policy experts of the nanotechnology industry, which number of 17 of them were selected as a sample according to the principle of theoretical saturation and with the purposeful sampling method. Also, the population of present study in the quantitative section was the managers and experts of small and medium businesses of nanotechnology industry whit number 1434 people, which 303 people of them were selected as a sample according to Cochran's formula and with the available sampling method. The data of the qualitative and quantitative sections were collected with methods of semi-structured interview and researcher-made questionnaires, respectively which whose psychometric indicators were confirmed and analyzed with methods of thematic analysis in MAXQDA software and exploratory factor analysis and structural equation modeling in SPSS and LISREL software, respectively.Findings: The findings of the first part of current research showed that the model of the role of entrepreneurial leadership in the performance of active small and medium businesses in the field of nanotechnology had 13 sub-factors in the 5 main factors of guidance, support, coaching, facilitation and entrepreneurship. Also, the findings of the second part of the present study showed that the factor load, average variance extracted and reliability of all factors were appropriate. In addition, the model of the role of entrepreneurial leadership in the performance of small and medium-sized businesses active in the field of nanotechnology had a significant effect on all five main factors and each factor with its sub-factors (P